Single-Unit Muscle Sympathetic Nerve Activity Reflects Sleep Apnea Severity, Especially in Severe Obstructive Sleep Apnea Patients - Hamaoka, Takuto; Murai, Hisayoshi; Kaneko, Shuichi; Usui, Soichiro; Okabe, Yoshitaka; Tokuhisa, Hideki; Kato, Takeshi; Furusho, Hiroshi; Sugiyama, Yu; Nakatsumi, Yasuto; Takata, Shigeo; Takamura, Masayuki (Frontiers in Physiology, 2016)
Obstructive sleep apnea syndrome (OSAS) is associated with augmented sympathetic nerve activity, as assessed by multi-unit muscle sympathetic nerve activity (MSNA). However, it is still unclear whether single-unit MSNA is a better reflection of sleep apnea severity according to the apnea-hypopnea index (AHI). One hundred two OSAS patients underwent full polysomnography and single- and multi-unit MSNA measurements. Univariate and multivariate regression analysis were performed to determine which parameters correlated with OSAS severity, which was defined by the AHI. Single- and multi-unit MSNA were significantly and positively correlated with AHI severity. The AHI was also significantly correlated with multi-unit MSNA burst frequency (r=0.437, p<0.0001) and single-unit MSNA spike frequency (r=0.632, p<0.0001). Multivariable analysis revealed that SF was correlated most significantly with AHI (T=7.27, p<0.0001). The distributions of multiple single-unit spikes per one cardiac interval did not differ between patients with an AHI of <30 and those with and AHI of 30 to 55 events/hour; however, the pattern of each multiple spike firing were significantly higher in patients with an AHI of >55. These results suggest that sympathetic nerve activity is associated with sleep apnea severity. In addition, single-unit MSNA is a more accurate reflection of sleep apnea severity with alternation of the firing pattern, especially in patients with very severe OSAS.